PENGARUH LAMA BETERNAK DAN PENDIDIKAN PETERNAK DENGAN PENGETAHUAN PETERNAK DALAM BIDANG REPRODUKSI TERNAK KERBAU DALAM UPAYA PENGEMBANGAN TERNAK KERBAU DI KABUPATEN PEMALANG - Erman Huza, Ulil Albab; Muatip, Krismiwati; Nugroho, Aras Prasetiyo (ANGON: Journal of Animal Science and Technology, 2023)
This study aims to determine the effect of length of time breeding and farmer education with knowledge of breeders in the field of buffalo reproduction in Pemalang Regency. The study used a survey method and the determination of the sample area was carried out by purposive random sampling by determining the area that had a large number of buffalo breeders. The sample area used is Surajaya Village representing Pemalang District, Kejambon Village representing Taman District, and Wanarata Village representing Bantarbolang District. Determination of respondents using the slovin formula with a margin of error of 10% obtained as many as 69 farmers. The analytical method used is descriptive analysis and multiple linear regression analysis. The results showed that the average length of breeding for buffalo breeders was 16 years, the average formal education of buffalo breeders is 3.5 years, and the knowledge of breeders in the field of reproduction is in the medium category. The results of multiple linear regression analysis showed that the length of husbandry and farmer's education simultaneously had a very significant effect on the knowledge of farmers in the field of reproduction (?<0.01). Partially, length of husbandryhad a significant effect on knowledge of breeders in the field of reproduction (?<0.05) and farmer education had a very significant effect on knowledge of breeders in the field of reproduction (?<0.01). The regression equation obtained is Y = 13.765 + 0.062X1 + 0.172X2. The coefficient of determination is 52.9% with a correlation coefficient of 0.727.